Judicial Analysis of Corruption Verdicts Concerning the Misappropriation of Social Assistance Funds During a National State of Emergency (Case Study of Decision No. 29/Pid.Sus-Tpk/2021/PN.Jkt.Pst) - Pangaribuan, Olwin Andrew; Putra, Mohammad Eka; Marlina, Marlina (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This study discusses the crime of corruption, where corruption is an act that is detrimental to the state, where the act is carried out in a matter that aims to enrich oneself, where this act of corruption is regulated in Law Number 31 of 1999 which is different from Law Number 20 of 200. This study uses a normative legal research method which uses secondary data as primary legal material, Criminal liability is a concept that determines whether a person can be punished for the actions he has committed. The elements of criminal liability are: the existence of a crime committed by the perpetrator, the existence of an element of error, the ability to be responsible and the absence of a reason for forgiveness. Criminal liability for corruption in social assistance funds is regulated in Article 2 paragraph 2 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption.